Predictors of leisure physical activity in a spanish university population - Ana Ponce-; Eva Sanz Arazuri (Sociedad Iberoamericana de Pedagogía Social, 2014)
Objectives: To determine some predictors of leisure-time physical activity in the Spanish university environment. Participants: A total of 1340 participants (48% men), with an average age of 22 years. Variables: leisure-time physical activity practice; gender; civil status; place of residence; amount of leisuretime; leisure-time occupation; desire to perform physical activity; satisfaction with the use of leisure-time; leisure-time physical activity practice in the past; and years of physical activity practice. Method: Face-toface interviews were undertaken using a questionnaire with close-ended questions. Results: Fifty-eight percent of the subjects reported being physically inactive. Male gender, desire to perform physical activity, satisfaction with the use of leisure-time, and practice of sports in the past, were significantly associated with leisure-time physical activity. Conclusions: Physical activity practice during childhood and adolescence is the strongest predictor of current leisure-time physical activity for this university population.